Capacity building in infrastructure for socio-economic growth and development: Malaysia and International Islamic University Malaysia (IIUM) as an ideal initiator and host of the 1st dedicated and construction focused training institution for the Muslim world? - Abdul Rashid, Khairuddin; Hasan, Sharina Farihah; Mohit, Mohammad Abdul; Aripin, Srazali (2013)
The paper initially discusses the concept of the Muslim World and highlights on the predicaments facing them in relation to socio-economic growth and development. The second part of the paper reviews the significance of construction to an economy focusing on the economies of the countries of the Muslim World. The outcome of the review suggests the construction sector in most of the countries have been performing below par so much so that they are acting as among the constraints in effort towards promoting and sustaining the countries’ socio-economic growth and development. The third part of the paper reviews the state of construction related training and education in the countries of the Muslim World focusing on training at tertiary levels. The outcome of the review suggests that credible and sufficient training programs and institutions to develop indigenous construction related skills and expertise are lacking and in some countries almost non-existence. Construction is significant to a country’s economy, irrespective of the country’s levels of socio-economic growth and development. It has been established that construction is more important to a developing country than to a developed country, notably due to the fact that construction provides the basic infrastructure that the developing country urgently requires in order to promote and sustain socio-economic growth and development. Acknowledging the connection between construction and socio-economic growth and development and the lack of capacity in the indigenous construction related skills and expertise, the fourth and final part of the paper proposes and discusses several strategies, the key strategy being the establishment of credible tertiary educational institutions dedicated to the studies of construction and construction related programs for the countries of the Muslim World. The paper concludes with a key recommendation and justifications on why Malaysia – in particular International Islamic University Malaysia (IIUM) – is considered the most ideal candidate to kick-start the initiative to set up the Muslim World’s first dedicated and construction focused tertiary institution.